Antifeminist Regress in Greece Today: The Politics of ‘Active Dads’ and ‘Fertility’ Campaigns - Alexandros Kioupkiolis; Christina Grammatikopoulou (Redescriptions)
This article examines the resurgence of antifeminist politics in Greece from 2010–2024, a period defined by economic and socio-political crises. It analyses how patriarchal, nationalist, and homophobic discourses have strategically targeted feminist and LGBTQIA+ rights, focusing on key actors, such as the Greek Orthodox Church, far-right groups, and new antifeminist factions that promote ‘men’s rights’ under the pretext of equality. The nub of our argument is that, in the context of intensified antifeminism in Greece in the critical years of 2010–2024, two critical cases, the 2021 ‘mandatory joint custody’ law and ongoing anti-abortion campaigns, constitute strategic and partly successful assaults on established women’s rights, marking a novel and disquieting development. To our knowledge, these events have not been extensively researched in recent social science studies despite their significance in reinforcing patriarchy and the way they reflect mutations of antifeminist politics in Greece today. This paper seeks primarily to contribute to a first mapping of this critical territory that remains uncharted to date. A more specific argument is that the end of this period witnessed the rise of a ‘fathers’ rights movement,’ which fully replicates the discursive frames and repertoires of action of the international ‘men’s rights movement.’ These transnational frames include the claim that men’s equal rights and children’s welfare are undermined under prevalent legal–institutional arrangements. Such ‘fathers’ rights politics’ poses new strategic threats to women’s rights and equality, requiring particular attention. Our study highlights the critical implications of these developments, which align Greece with the global rise of authoritarian, antifeminist movements and serve to consolidate patriarchal power structures.